Enlarged current injection model for the power flow solution of unbalanced distribution networks - Rubén Carmona-Pardo; Álvaro Rodríguez del Nozal; Esther Romero-Ramos; Antonio Gómez-Expósito (International Journal of Electrical Power & Energy Systems)
This paper presents an approach for the power flow solution of three-phase, four-wire unbalanced distribution networks. The proposed formulation uses rectangular coordinates and, unlike most earlier approaches, both bus voltages and injected currents are retained as variables. The Newton–Raphson method is then applied to the augmented system of equations, resulting in an iterative process that is solved optimally. All together, this scheme constitutes a novel solution to the power flow problem of unbalanced distribution networks, leveraging its enhanced numerical conditioning to improve the convergence rate. A thorough analysis of the proposed approach on several real-life distribution networks demonstrates its performance and robustness, when compared to the conventional current injection method.